Step-by-step explanation:
step 1. the cube root is also to the 1/3 power
step 2. (27a^3b^7)^(1/3) = (3*3*3*a*a*a*b*b*b*b*b*b*b)^(1/3)
step 3. a third root: 3 factors in the root comes "out" of the root as 1
step 4. 3ab*b(b)^(1/3) = 3ab^2(b)^(1/3).
Don't understand the question your asking
Answer:
see attached
Step-by-step explanation:
The equation is in the form ...
4p(y -k) = (x -h)^2 . . . . . (h, k) is the vertex; p is the focus-vertex distance
Comparing this to your equation, we see ...
p = 4, (h, k) = (3, 4)
p > 0, so the parabola opens upward. The vertex is on the axis of symmetry. That axis has the equation x=x-coordinate of vertex. This tells you ...
vertex: (3, 4)
axis of symmetry: x = 3
focus: (3, 8) . . . . . 4 units up from vertex
directrix: y = 0 . . . horizontal line 4 units down from vertex
Answer:
12
Step-by-step explanation:
Answer:
$1 every 3 minutes
Step-by-step explanation:
Cause every 36 minutes Scarlett earns $12 and if you divide 36 by 12 it will give 3 minutes which means she earns $1 per 3 minutes. You're right.